Blooket: Alternative media for Arabic vocabulary learning for university students in Islamic boarding schools - Ahmad Fatoni; Mochammad Firdaus; Ahmad Hafidz Abdullah; Faris Maturedy; Utari Dwi Mayasari; Primasti Nur Yusrin Hidayanti (Universitas Muhammadiyah Malang, 2024)
The utilization of digital platforms is one of the key factors in the success of learning activities. This applies to Arabic language learning activities for specific purposes for students. Instructors and teachers can leverage digital platforms to provide students with new experiences in the learning process. One digital platform that can serve as an alternative medium is Blooket. This study aims to explore Arabic language classes for specific purposes with the aid of an educational game platform. Therefore, the researcher employs qualitative research to gain an in-depth understanding of the various phenomena occurring during these activities. The researcher uses observation techniques to monitor the atmosphere and interactions among students during the class. Documentation is also used to gather data in the form of supporting documents for these activities. The data is then analyzed using the Miles, Huberman, and Saldana analysis model, which consists of three stages: data condensation, data presentation, and conclusion drawing. The results of the study indicate that Arabic language classes for specific purposes consist of several activities. First, the instructor begins with an introduction to the Arabic language for the purpose of pilgrimage by inviting a pilgrimage guide. The skill focus of the learning is vocabulary mastery related to the conduct of the pilgrimage. Next, the instructor uses the educational game platform Blooket to motivate students and provide them with a new and engaging learning experience in Arabic. Students enthusiastically participate in the series of class activities. In addition, they gain new experiences regarding the use of the Blooket digital platform in Arabic language learning.